If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -16 + 5y = -59 Reorder the terms: -16 + 8y + 5y = -59 Combine like terms: 8y + 5y = 13y -16 + 13y = -59 Solving -16 + 13y = -59 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 13y = -59 + 16 Combine like terms: -16 + 16 = 0 0 + 13y = -59 + 16 13y = -59 + 16 Combine like terms: -59 + 16 = -43 13y = -43 Divide each side by '13'. y = -3.307692308 Simplifying y = -3.307692308
| s(s)+10s+24=0 | | 7=4x-5 | | 50-2h=44 | | 4x-8=28-x | | -15x=23(4+4)/(-23) | | 4(-7+x)=5x-1/4 | | -15x=23(4+4)/23 | | c/5+8=-5 | | 8/3+2.4 | | 18+9m=288 | | 15x=23(4+4)/23 | | 9x+4=1+2x | | x+7/4=8/5 | | 2.8x-3.3=-8.9 | | 2(9x+7)-8x=2(5x+4)-12 | | -3c-2+7=4c+2-6c | | -8-6x=28 | | 6y+3=5y-9 | | 2(x-1)=4x+1 | | -12+20p=588 | | 4/3x=52 | | n-(0.05xn)=10000 | | 5(y+7)+y=2(y+5)+6 | | 3(2x-10)(7x-70)=0 | | 16x^2-48x+36=0 | | 16x^2-48x+36=0 | | 7+2x=3x+8 | | -17=-204 | | 3x/9x^2-6x | | 5(2-y)/2=-y | | 0.2f+06(f+20)=-8+0.4f | | y^2-(5/3)y=-(25/36) |